The Implementation of Total Quality Management at MAN 2 Bogor - Norman, Efrita (Jurnal Manajemen, 2019)
This research is aimed to analyze TQM model that has been applied in MAN 2 Kota Bogor. This research also tried to find the implemented solution and strategies to enhance the implementation of TQM in MAN 2 Kota Bogor. This study is investigating the phenomenon that occurs in Madrasah environment, according to behavior, perception, motivation, action, etc. Research Object in this study is fundamental behavior that is suspended from the researcher observations, and then this study used qualitative research approaches. But to strengthen the data collected, quantitative approaches are used through survey. This study is explorative study to formulate quality management concept in education institutions of MAN 2 Kota Bogor. Research method used in this study is descriptive explorative and Analytical Network Process (ANP). The research result show that MAN 2 Kota Bogor has been applied TQM gradually. All school components contributed in TQM implementation in MAN 2 Kota Bogor, such as head of school, teachers, administration staff, and all management divisions has their own functions and role. Solutions to the problems appeared based on the priorities are focus on the customers, followed by SOP to all of school activities, sustainability improvement, commitment, management process measurement, and total involvement. The strategies offered to enhance the implementation of TQM in MAN 2 Kota Bogor based on the priorities are human resource empowerment, followed by empowering teacher’s discipline, develop powerful coordination, curriculum preparation, evaluation each semester, and giving trust to teachers.